Economic and Mathematical Modeling of Complex Cooperation of Academic Staff of Educational Cluster on the Basis of Fuzzy Sets Theory - Tishchenko, Evgeniy N; Sharypova, Tatyana N; Zhilina, Elena V; Cherkezov, Saveliy E (Journal of Applied Economic Sciences (JAES), 2016)
The article substantiates necessity for development of fuzzy models for evaluation of cooperation level of academic staff of educational cluster on the basis of fuzzy sets theory, which allow performing integral accounting of qualitative input/output parameters. Methodology of complex of fuzzy models is brought down to analysis of problem situation and structuring of subject sphere, development of fuzzy models, execution of calculation experiments with fuzzy model, application of results of calculation experiments, and correction of fuzzy model. The authors develop a complex of fuzzy models for evaluation of cooperation level of academic staff of educational cluster, which includes the following models in the basis of fuzzy sets theory: model of evaluation of cooperation of academic staff of university chair, which is a part of a cluster; model of evaluation of post- graduate system of professional training for academic staff of cluster; model of evaluation of developed strategy of cooperation of academic staff of cluster; model of evaluation of cooperation of cluster multiplier; model of evaluation of development of mobile innovational group of cluster; model of formation of linguistic evaluation of students’ success in studying; model of evaluation of use of cluster web- resources. Modeling is realized by means of MATLAB with the use of specialized package Fuzzy Logic Toolbox on the basis of fuzzy inference of the Mamdani algorithm.